Regionally progressive accumulation of iron in Parkinson's disease as measured by quantitative susceptibility mapping. (8th February 2016) - Guan, Xiaojun; Xuan, Min; Gu, Quanquan; Huang, Peiyu; Liu, Chunlei; Wang, Nian; Xu, Xiaojun; Luo, Wei; Zhang, Minming
Abstract : The progression of Parkinson's disease (PD) seems to vary according to the disease stage, which greatly influences the management of PD patients. However, the underlying mechanism of progression in PD remains unclear. This study was designed to explore the progressive pattern of iron accumulation at different stages in PD patients. Sixty right‐handed PD patients and 40 normal controls were recruited. According to the disease stage, 45 patients with Hoehn–Yahr stage ≤ 2.5 and 15 patients with Hoehn–Yahr stage ≥ 3 were grouped into early‐stage PD (EPD) and late‐stage PD (LPD) groups, respectively. The iron content in the cardinal subcortical nuclei covering the cerebrum, cerebellum and midbrain was measured using quantitative susceptibility mapping (QSM). The substantia nigra pars compacta (SNc) showed significantly increased QSM values in the EPD patients compared with the controls. In the LPD patients, while the SNc continued to show increased QSM values compared with the controls and EPD patients, the regions showing increased QSM values spread to include the substantia nigra pars reticulata (SNr), red nucleus (RN) and globus pallidus (GP). Our data also indicated that iron deposition was more significant in the GP internal segment (GPi) than in the GP external segment. No other regions showed significant changes in QSM values among the groups. Therefore, we were able to confirm a regionally progressive pattern of iron accumulation in the different stages of PD, indicating that iron deposition in the SNc is affected exclusively in the early stages of the disease, while the SNr, RN and GP, and particularly the GPi segment, become involved in advanced stages of the disease. This is a preliminary study providing objective evidence of the iron‐related progression in PD. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Quantitative susceptibility mapping was used to confirm a regionally progressive pattern of iron accumulation in patients with Parkinson's disease (PD) at different stages, which indicates that iron deposition in the substantia nigra pars compacta (SNc) is affected exclusively in the early PD (EPD) patients, while the substantia nigra pars reticulata (SNr), red nucleus (RN) and globus pallidus internal (GPi) as well as globus pallidus external (GPe) become involved in the late PD (LPD) patients.